Dehydroepiandrosterone sulphate (DHEAS) supplementation impacts adrenal cortex morphophysiology of aged female gerbils - Bedolo, Carolina Marques [UNESP]; Cozim, Isabella Carolina; Grigio, Vitor [UNESP]; Bernussi, Gabriel Ribeiro [UNESP]; Silva, Stella Bicalho [UNESP]; Guerra, Luiz Henrique Alves [UNESP]; Campos, Silvana Gisele Pegorin [UNESP]; Vilamaior, Patricia Simone Leite [UNESP]; Leonel, Ellen Cristina Rivas; Taboga, Sebastião Roberto [UNESP] (Elsevier, 2025)
During the process of aging, it is common for women to take dehydroepiandrosterone sulphate (DHEAS) supplements to prevent adrenopause. However, the potential effects of this supplementation on the adrenal cortex have not yet been fully elucidated. Therefore, the present study aimed to analyze the effects of DHEAS supplementation on the adrenal cortex of female Mongolian gerbils during the aging process. The experiment was conducted by dividing the aged female gerbils (18 months of age) into two groups (n = 5). The control group received no treatment, while the experimental group received 60 mg/kg of DHEAS for 5 weeks. The adrenal glands of both groups were then subjected to morphological, hormonal and immunohistochemistry analyses. The results showed that DHEAS supplementation led to a significant increase in the accumulation of lipofuscin granules in the adrenal cells. Furthermore, decreases in ERα and ERβ and the enzymes CYP17 and 17βHSD, and an increase in the 5α-reductase enzyme in the adrenal cortex were also observed. The results suggest that DHEAS supplementation has a negative feedback effect on the adrenal cortex, affecting its morphophysiology and, consequently, the gland's functionality. In addition, DHEAS supplementation does not reverse all aspects of the effects of aging on adrenal gland homeostasis.